RUSSIAS ECONOMIC RELATIONS WITH FOREIGN COUNTRIES IN THE LAST QUARTER OF THE XIX CENTURY AND THE BEGINNING OF THE XX CENTURY: https://doi.org/10.5281/zenodo.14722836 - Zakirov , Jasur (International scientific and practical conference, 2024)
This article, from a historical point of view, provides a comprehensive analysis of the development of Russia’s economic links with foreign countries in the last quarter of the 19th - early 20th century. The main attention is paid to the consideration of the role and significance of these links in the overall economic development of the Russian state. Issues such as customs policy, attraction of investments and development of foreign trade, which are priorities in the field of foreign economic activity, are covered on the basis of specific data.